Cryotherapy as A Prophylaxis of Mucositis in Children with Cancer Undergoing Chemotherapy at Dr. M. Djamil General Hospital - Hidayatul Hasni; Mayetti Mayetti; Dwi Novrianda (Indonesian Journal of Cancer, 2021)
Background: Mucositis is one of the side effects of chemotherapy, which can be a severe problem for children with cancer. Cryotherapy can cause vasoconstriction and decrease blood flow to the oral mucosa, resulting in lower concentrations of chemotherapy agents to prevent mucositis. This study aims at determining the effectiveness of oral cryotherapy as prophylaxis mucositis in children with cancer undergoing chemotherapy.Methods: This quasi-experiment study with a pretest-posttest control-group design involved 45 respondents (22 in the intervention group and 23 in the control group) selected using consecutive sampling. The data collection instrument was the WHO mucositis scale. Results: Of the 45 children undergoing chemotherapy, 24 (53.3%) were of school age, 25 (55.6%) were male, 33 (73.3%) had good nutritional status, and 17 (37.8%) had mild neutropenia before undergoing chemotherapy. All respondents (100%) did not experience mucositis, but after chemotherapy, 9 children (40.9%) in the intervention group had mucositis, and 19 children (82.6%) experienced mucositis in the control group. The data were analyzed using the Wilcoxon test to see the difference between the intervention group and the control group and the Chi-Square test with Yates’s correction to see the effect of cryotherapy on the prevention of mucositis. The results showed that there was a difference in the incidence of mucositis between before and after intervention in the intervention group (p = 0.003) and the control group (p = 0.000), and cryotherapy was effective in preventing mucositis (p = 0.01).Conclusions: Cryotherapy is effective against the prevention of mucositis. Nurses and families need to be able to apply oral cryotherapy and other evidence-based treatment as a method to prevent mucositis